Development Of Creative Competence In Preschool Children - Toshpulatova, Inobatkhon (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This article covers the pedagogical foundations and methods of forming and developing creative competence in preschool children. Creative competence is important in forming new thinking, creativity, non-traditional approaches to problems and independent decision-making skills in children. During the study, modern pedagogical technologies, interactive games, creative exercises and project-based activities that serve to develop creativity were analyzed. The article also developed methodological recommendations and indicated the possibilities of their application in preschool education practice. It was noted that the results serve to develop children's thinking, form independent thinking and strengthen their communicative competence.